Students' perceptions of translation strategies in French and Malay language: a qualitative approach - Abdul Halim, Hazlina; Ang, Lay Hoon; Mansor, Nor Shahila; Mamat, Roslina (Serials Publications, 2016)
Translation plays a key role in foreign language learning and teaching. After the application of translation in Grammar Translation Method, the method had been inadvisable in classroom teaching and learning. However, translation strategies are undeniably one of multiply factors on achieving learners' target on acquiring a foreign language. Thus, this exploratory study aims to analyze Malaysian students' perception in applying translation to learn French and French students perceptions in applying translation to learn Malay as a foreign language. The respondents for this research were 20 Malaysian students learning advanced French from Universiti Putra Malaysia and 20 French students learning advanced Malay from Institut Nationale des Langues et Civilisations Orientales, France. The study utilized qualitative method of data collection by using interviews as an instrument to investigate the perception of translation strategies by learners of both languages. The results showed that Malaysian students found translation strategies as a good and best way to learn French, whereas French students find translation is merely a tool for beginners and learning should be conducted in the target language. The result of the study is hoped to guide language instructors to consider to use or not to use translation as a part of their Malay and French teaching tools.